PELATIHAN DIGITAL MARKETING BAGI PAM JEMAAT I.S KIJNE ABEPURA, JAYAPURA - Jonathan K. Wororomi; Remuz M.B. Kmurawak; Mingsep Rante Sampebua (JURNAL PENGABDIAN PAPUA, 2023)
The problem with the Youth Fellowship at GKI I.S Kijne Abepura congregation is that they do not have the skills and abilities to use information technology for digital marketing. The purpose of the Uncen PNBP service in 2022 is to transfer science and technology for PAM at GKI Congregation I.S Kijne Abepura so that they can increase innovation, skills and abilities in conducting digital marketing. Community service activities are carried out using lecture, discussion, question and answer methods, practice, and evaluation. The stages of implementation include planning, conducting training, evaluating activities, and reporting. The results achieved from the Uncen PNBP dedication are that young people in the GKI Congregation I.S Kijne Abepura have knowledge, skills, and can sell online on the online business platform tokopedia.com.Ã‚Â Keywords: PAM; GKI I.S Kijne; Tokopedia; Digital Marketing; TrainingÃ‚Â